(untitled) (Journal of Parents and Teachers, 2023)
In this article we will see different strategies to implement PD in an educational center, we will know some of the schools that are carrying it out and we will share the day to day of what we do in the classroom to promote this cultural change in a school. All this, with the objective to develop socio-emotional skills in both our students and our staff and to create a culture based on respect, belonging and significant of all its members.